Prevalence and severity of molar-incisor hypomineralisation with relation to its etiological factors among school children 7- 9 years of Al-Najaf governorate - Walaa A Ofi; Ban A Salih (College of Dentistry/ University of Baghdad, 2015)
Background: Molar Incisor hypomineralisation (MIH) is one of the biggest challenges with great clinical interest. Currently, the etiology of MIH remains unclear. There is no previous study concerning school children aged 7 - 9 years in Al-Najaf governorate in order to estimate the prevalence and severity of molar incisor hypomineralisation and the possible associated risk factors. This study aimed to estimate the prevalence, severity and the possible associated etiological factors of molar incisor hypomineralisation and also to study the correlation between body mass index and molar incisor hypomineralisation. Material and Methods: Across sectional study conducted at Al-Najaf Governorate. A total of 600 children were enrolled those who did not met the inclusion criteria were excluded. A structured self-administered validated Arabic language questionnaire and an examination sheet were used for data collection. Body weight and height were measured and the body mass index was calculated. Dental material and supplies were used in examination. The demarcated hypomineralization was recorded according to the 10 point scoring system depended on the EAPD evaluation criteria The severity was assessed according to the clinical evaluation of the examiner and the presence of opacities. Results: The response rate was 84.7% and the highest was in the 9-year-old children, the participants were 532 children, the prevalence of hypomineralisation defect was 22.9%. The prevalence of demarcated hypomineralisation was increased concomitantly with the age, and the 9-year-old children were the more affected. The overall prevalence of MIH among boys was lower than girls; (17.3%) and 22.6%, respectively. The severely affected teeth were 33/1464 teeth, represented 2.3%, severely affected molars were 25 (5.1%) and the severely affected incisors were 8 (0.8%). More severely affected teeth were found in obese and overweight children were also increased with the age of child. Conclusions: The prevalence of Molar Incisor Hypomineralisation in this study was 22.9%, MIH was more prevalent among girls, the 9-year-old, normal body weight and urban residents children. The severely affected teeth represented 4.5% of the total number of teeth, molars were more severely affected than incisors, obese and overweight children and older children have more severe MIH. Further studies are suggested.